Evaluating Data Quality in the Cancer Registry - BRAY, FREDDIE (Indonesian Journal of Cancer, 2010)
Evaluating Data Quality in the Cancer RegistryÂ Â Full text : http://www.scribd.com/doc/43593006/Evaluating-Data-Quality-in-the-Cancer-Registry